Overview of Anxiety Levels in Primigravida Pregnant Women Approaching Labor in Tambaan Village, Camplong District, Sampang Regency - hidamansyah, Murfi; Jayanti, Nur; Fithriani, Zainun Wahida; Sholihah, Imroatus (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Mental health problems or disorders are disturbances in thoughts, feelings, and behavior, causing suffering and impaired daily functioning both personally and socially. Mental health during pregnancy is an important aspect that affects the well-being of the mother and fetal development. Pregnant women often experience significant emotional and physical changes, which can trigger stress and anxiety.Objective: This study aims to determine the level of anxiety in pregnant women approaching labor.Methods: The type of research used in this study is descriptive. The research was conducted in Tambaan Village, Camplong District, Sampang Regency. The population consisted of all third-trimester pregnant women. The sample was 25 pregnant women. The criteria for this study were pregnant women willing to be respondents and pregnant women without pregnancy-related complications.Results: The study results showed that 8% experienced mild anxiety, 72% moderate anxiety, and 20% severe anxiety. Conclusion: This study concluded that the majority of pregnant women in Indonesia experience anxiety in facing childbirth with varying levels. Primigravida mothers most commonly experienced moderate anxiety, followed by severe and mild anxiety. Recommendation: It is recommended that pregnant women increase antenatal care visits to prepare themselves physically and mentally for childbirth. Keywords: Characteristic Overview, Primigravida, Anxiety